Muhammadiyah dan Transformasi Pendidikan di Era Modern - Zumrotil Auliya; Indah Dewi Permata Sari; Lily Ervina Putri; Irghi Edwin Afando; Wismanto Wismanto; Wira Ramashar (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This writing discusses about islamic education which gets some crusial challenges in globalization era. Islamic teaching plays important role in globalization. Since globalization itself has possitive also negative in islamic teaching and training. Thus, reformation of islamic teaching could strive for raising better vision of islamic teaching for building and upgrading quality of human being and moslem society in globalization that ought to refer to both Al Koran and Al Hadith as source of its teaching. Since its establishment in 1912, Muhammadiyah has made significant contributions to advancing education in Indonesia through various innovative initiatives. This study employs a qualitative approach with a case study method, involving in-depth interviews, observations, and document analysis from various Muhammadiyah educational institutions. The findings indicate that Muhammadiyah has successfully integrated technology into learning, developed a competency-based curriculum, and improved the quality of human resources. However, the organization also faces challenges, such as educational access disparities, technology implementation, and the influence of globalization on local values. The conclusion of this study emphasizes the importance of collaboration among Muhammadiyah, the government, and society to create inclusive and sustainable education. With a strong commitment to character and moral education, Muhammadiyah plays a vital role in shaping a generation that is not only intelligent but also possesses integrity and social awareness.